Analisis Pengaruh NPF, FDR, BOPO, CAR, dan GCG terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia Periode 2013-2017 - Suwarno, Rima Cahya; Muthohar, Ahmad Mifdlol (Universitas Islam Negeri Sunan Kudus, 2018)
This study aims to determine the Influence of NPF, FDR, BOPO, CAR, and GCG on Financial Performance of Sharia Commercial Banks in Indonesia Period 2013-2017. This research use quantitative research method with population in this research is all sharia commercial bank in Indonesia period 2013-2017. The total sample is eight of sharia commercial banks, based on purposive sampling method. Data collection is done by library method from journals, articles or literatures that related to required data, and documentation method of annual report and GCG implementation report of sharia public bank in question as well as data from OJK website. The research method used is statistical descriptive test, descriptive test by analyzing GCG through GCG implementation report using content analysis method, classical assumption test, multiple regression test. The results showed that simultaneously NPF, FDR, BOPO, CAR, and GCG variables significantly influence the Financial Performance of Sharia Commercial Banks in Indonesia Period 2013-2017. While the partial variable of NPF has positive effect not significant to ROA, FDR variable has positive effect not significant to ROA, BOPO variable has significant negative effect to ROA, CAR variable has positive effect not significant, and GCG variable has positive effect not significant to ROA of Sharia Commercial Bank in Indonesia 2013-2017 period.